Episodic Literary Movement and Translation: Ideology Embodied in Prefaces - Khademnabi, Mir Mohammad (Text Matters: A Journal of Literature, Theory and Culture, 2021)
This paper discusses translation practices from a historicist viewpoint, contextualizing them in their emerging “episode.” The latter is a concept drawn from sociology of literature and accounts for the rise of certain discourses and ideologies in a society. On the basis of the argument that translation practices are informed by the general literary and socio-cultural milieu in which they are produced and consumed (also known as ideology of representation), the paper studies the translators’ prefaces to three translations published between 1953 and 1978—a period dominated by Leftist and Marxist discourse in Iran. Drawing on a historically oriented model which holds that the translator’s ideology is revealed at the moment in which he/she chooses a text, and continues through the discourse he/she develops to translate that text, the research embarks on studying translation practices on two levels of choice mechanism and prefaces. Prefaces are discussed in the light of the dominant ideology of representation that is characterized by a revolutionary discourse. The research demonstrates that these translators opted for a strategy that incorporates the translations in the Persian cultural setting with minor changes in a way that politicizes the foreign literature.